UKRAINIAN-AUSTRALIAN LITERARY HORIZON: CHALLENGES OF ESTABLISHMENT - Usatenko, Galyna; Usatenko, Tamara (Київський національний університет імені Тараса Шевченка, 2021)
The article considers the role of Ukrainian literature in the preservation of native culture in Australia of immigrants from Ukraine in the first wave of settlement and the decline of interest in literature in the country of emigrants in the next waves of arrival. The increased attention of the first Ukrainian immigrants to fiction as a unique factor in preserving the mentality in the multicultural society, the formation of public identity, the development of worldview and cognitive, socio-humanitarian, sociopolitical beliefs of the community, each individual. Stages, forms, methods, approaches in the organization of mass literary education of Ukrainian settlers, the activity of literary, non-literary (cultural, sports, professional), commercial and noncommercial structures of the community in the organization of literary process is revealed: selection for reading of classical literature, financial support of writers, participation in printing literary texts, distributing, filling libraries with literature, etc. The contribution of book lovers' circles to the unity of the community, improvement of communication, personal relations, raising interest in reading Ukrainian literature, comprehension of the content of what is read is proved. The role of writers, writers' associations, organizations, literary studios, scientists, public activists in the development of cultural, artistic, literary, educational processes has been studied. The special role of Ukrainian studies centers of universities in Australia in the development of scientific foundations of education, literary studies simultaneously with the solution of economic and economic development, integration into the civil society of the state of Australia. The isolation of the factors of Ukrainian studies from the basis of Ukrainian studies is substantiated. Attention is paid to modern literary studies of the young gener ation of Ukrainian scientists born in Australia (field theory, network, art aesthetics, etc.) through the prism of postmodernist ideas of Western European culture. It is noted about the integration of the Ukrainian literary network into the Australian socio-cultural space. The connections and cooperation of Ukrainian studies centers in Australia with literary institutions of Ukraine, international scientific literary studies, Ukrainian studies centers are highlighted. The emergence of conflicts, conflicts of interest, desires, understanding of opposing views that appear in the process of communication between Ukrainian immigrants of the first wave of settlement and the representatives of the next stages, the preconditions of which are based on objective and subjective conditions. It is noted that the joint solution of inconsistencies based on cooperation and the development of constructive decisions is far from a positive clarification. Challenges, inconsistencies of the emigrant community of the first and subsequent waves of settlement, difficulties of preservation of identity, language, traditions, culture in the multicultural environment are found out.

У статті розглядається роль української літератури у збереженні іммігрантами з України першої хвилі поселення в Австралії своєї культури та згасання інтересу до літератури в емігрантів-земляків наступних хвиль прибуття. Охарактеризовано посилену увагу перших українських переселенців до художньої літератури як унікального фактору збереження в умовах полікультурного суспільства ментальності, формування громадської ідентичності, розвитку світоглядно-когнітивних, соціо-гуманітарних, суспільно-політичних переконань громади, кожної особистості. Розкрито етапи, форми, методи, підходи в організації масової літературної освіти українських поселенців, активну діяльність літературних, нелітературних (культурних, спортивних, професійних), комерційних і некомерційних структур громади в організації літературного процесу: відбору для читання класичної літератури, фінансова підтримка письменників, участь у друкуванні літературних текстів, поширенні, наповненні літературою бібліотек тощо. Доведено внесок гуртків книголюбів у єднання спільноти, поліпшення спілкування, особистісних стосунків, підняття зацікавленості до читання української літератури, осмислення змісту прочитаного. Досліджено роль письменників, письменницьких асоціацій, організацій, літературних студій, вчених, громадських активістів в розгортанні культурно-мистецьких, літературних, літературознавчих, освітніх процесів. Відзначена особлива роль українознавчих центрів університетів в Австралії в розробці наукових основ літературної освіти, літературознавчих досліджень одночасно з вирішенням економічно-господарського облаштування, інтеграцією в громадське суспільство держави Австралія. Обґрунтовано вичленення з основ українознавства чинників україністики, україніки. Увагу приділено сучасним науковим літературознавчим дослідженням молодої генерації вчених-українців, народжених в Австралії (теорії поля, мережі, естетики мистецтва та ін.) крізь призму постмодерністських ідей західноєвропейської культури. Охарактеризовано процес «вбудовування» українського літературного процесу в австралійський соціокультурний простір. Виокремлено зв‘язки і співпрацю українознавчих центрів в Австралії з літературними інституціями України, міжнародними науковими літературознавчими, українознавчими центрами. З‘ясовано виникнення конфліктів, зіткнень інтересів, бажань, розуміння протилежних поглядів, що з‘являються в процесі спілкування між українськими іммігрантами першої хвилі поселення та представниками наступних етапів, передумови яких базуються на об‘єктивних та суб‘єктивних умовах. Відзначено, що спільне рішення неузгодженостей на основі співробітництва і вироблення конструктивних рішень далеке від позитивного вирішення. Виокремлені виклики, неузгодженості емігрантської громади першої та наступних хвиль поселення, складності збереження ідентичності, мови, традицій, культури в полікультурному середовищі.
УКРАЇНСЬКО-АВСТРАЛІЙСЬКЕ ЛІТЕРАТУРНЕ ВИДНОКОЛО: ВИКЛИКИ СТАНОВЛЕННЯ
Keywords: literature; Ukrainian literature in Australia; the first wave of settlement of Ukrainian immigrants; centers of Ukrainian studies; reading; book lovers' circles; transformation; assimilation; international relations; література; українська література в Австралії; перша хвиля поселення українських іммігрантів; центри українознавства; читання; гуртки книголюбів; трансформація; асиміляція; міжнародні зв‘язки